2010
DOI: 10.1017/s1461145710000684
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 receptors in the medial prefrontal cortex modulate the expression of contextual fear conditioning

Abstract: The ventral portion of the medial prefrontal cortex (vMPFC) has been related to the expression of contextual fear conditioning. This study investigated the possible involvement of CB1 receptors in this aversive response. Male Wistar rats were submitted to a contextual aversive conditioning session and 48 h later re-exposed to the aversive context in which freezing and cardiovascular responses (increase of arterial pressure and heart rate) were recorded. The expression of CB1 receptor-mRNA in the vMPFC was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0
20

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 58 publications
7
55
0
20
Order By: Relevance
“…2008), and vmPFC (Lisboa et al, 2010) to the observed effects should be examined in a future study. In addition, because this memory is essential for individuals' survival, it seems that a warning is necessary in excessive reduction of this memory.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2008), and vmPFC (Lisboa et al, 2010) to the observed effects should be examined in a future study. In addition, because this memory is essential for individuals' survival, it seems that a warning is necessary in excessive reduction of this memory.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, systemic administration of the CB 1 agonists WIN55,212-2 (WIN) or HU-210 impairs contextual fear conditioning in rats (Mackowiak et al, 2009;. In addition, pre-test microinjection of another CB 1 agonist, anandamide, into the dorsolateral periaqueductal gray (PAG) or ventromedial prefrontal cortex (vmPFC) impairs contextual fear conditioning in rats (Lisboa et al, 2010;Resstel et al, 2008). These results consistently suggest that activation of CB 1 receptors reduces contextual fear memory.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, results from our group showed that expression of mRNA for CB 1 receptors in the vMPFC is increased in animals exposed to a protocol of contextual fear conditioning. Moreover, when these animals were treated with the CB 1 receptor antagonist AM251 in the vMPFC, they exhibit an increase of both cardiovascular and behavior responses associated with reexposure to the aversive context (30). Finally, the local administration of an antagonist of NMDA receptors in the vMPFC evokes a decrease of both cardiovascular and behavior responses associated with contextual fear conditioning (47).…”
Section: Discussionmentioning
confidence: 99%
“…All groups of animals used in our study received three sets of phenylephrine or SNP infusion to determine control values of baroreflex activity. In the sequence, the first group received a microinjection of 200 nl of 10% DMSO dissolved in saline (0.9% NaCl); the second group received a microinjection of 200 nl of AM251 [10, 100, or 300 pmol (30)]; the third group received a microinjection of 200 nl of AM404 [50 or 100 pmol (30)]; the fourth group received a microinjection of 200 nl of URB597 [100 pmol (31)]; the fifth group received bilateral microinjections of 200 nl of AM251 (10 pmol) and 5 min later AM404 (100 pmol) or URB597 (100 pmol). In all experimental groups, phenylephrine and SNP infusions were repeated 10 and 60 min after the microinjection of drugs.…”
Section: Methodsmentioning
confidence: 99%
“…O CPFMv está envolvido com a modulação de respostas emocionais e autonômicas em situações aversivas (Lisboa et al, 2010b Como os sistemas endovanilóide e endocanabinóide presentes no CPFMv interagem entre si (Fogaca et al, 2012), o bloqueio de receptores CB1 do CPFMv, poderia deslocar a anandamida para a ativação de receptores TRPV1, o que pode ser responsável pelo aumento do comportamento do tipo ansiogênico e das alterações cardiovasculares associados ao contexto aversivo (Lisboa et al, 2010a). Deste modo, os receptores TRPV1 presentes no CPFMv também podem participar da modulação barorreflexa durante reações de defesa, podendo estar envolvidos, por exemplo, nos ajustes que facilitam a taquicardia reflexa observada em ratos submetidos ao modelo do estresse por restrição (Crestani et al, 2010), permitindo também o aumento de PA concomitante ao aumento de FC, característico da resposta autonômica que acontece durante situações aversivas (Resstel et al, 2008).…”
Section: -Discussãounclassified